Peningkatan Hasil Belajar Sistem Persamaan Linier Di Kelas VIII C MTs. Negeri 2 Mojokerto Melalui Pembelajaran Berbasis Masalah - Sungkono (Indonesian Journal of Integrated Science and Learning, 2024)
Mathematics learning in class VIII C MTs. Negeri 2 Mojokerto, experienced problems. In the daily test on systems of linear equations, the class average score obtained was very low, namely 58.8. There were 21 students who had achieved learning completeness or 56.8%. Action research aims to describe the application of problem-based learning in mathematics learning and to find out whether the application of problem-based learning can improve learning outcomes for systems of linear equations. This research is action research. Based on the research that has been carried out, it is concluded that the application of problem-based learning can improve mathematics learning outcomes regarding systems of linear equations in class VIII C MTs. Negeri 2 Mojokerto. This is based on an increase in pre-cycle learning outcomes of 5.01, with a learning completion percentage of 21.6%. In the first cycle, the average post test result was 70.8, with a learning completion percentage of 40.6%. Meanwhile, the average second cycle post test result was 8.56, with a learning completion percentage of 91.9%.